ESG perception on Fintech companies - Iskandar, Riko; Hermawan*, Marko S (Riviera Publishing, 2025)
This study aims to explore the perceptions of fintech companies in Indonesia regarding the implementation of Environmental, Social, and Governance (ESG) principles and the challenges faced in their application. The research employs a qualitative method with a case study approach, where data were collected through in-depth interviews with practitioners and employees experienced in ESG within fintech companies, resulting in interview transcripts. The findings reveal that fintech companies have begun integrating ESG into their operations and decision-making processes, although there is variation in the level of adoption and implementation. Several key challenges were identified, including gaps in ESG reporting, lack of standardization, and pressure from investors to enhance transparency. Additionally, fintech companies demonstrate a strong commitment to social aspects, such as financial inclusion and community empowerment, as well as efforts to ensure environmentally friendly operations. The study also finds that while progress has been made in applying ESG principles, further efforts are needed to improve the quality of reporting and comprehensive integration of ESG into business strategies. The conclusion of this research is that fintech companies in Indonesia have the potential to contribute to sustainability through the application of ESG principles; however, existing challenges must be addressed to achieve optimal outcomes.